Peran Pemuda dalam Pengembangan Perekonomian Perspektif Ekonomi Syariah: Studi pada UMKM di Kecamatan Pemangkat - Destia Nur Fitri; Iva Ashari Ananda; Marina (Ekodestinasi, 2025)
Entering the post-pandemic demographic dividend era, youth play a crucial role in transforming from job seekers to job creators. This study uses a descriptive-analytical qualitative approach based on field research. The research subjects consisted of 12 youth MSME actors (aged 18-30 years) from various sectors selected purposively. Primary and secondary data collection were carried out simultaneously through participatory observation, in-depth interviews, and documentation techniques. The collected data were then analyzed using an interactive model that includes data reduction, data display, and conclusion drawing. The results show that youth make concrete contributions to reducing the unemployment rate through the creation of new jobs, the utilization of accelerated digital marketing, and the creation of product innovations. Despite facing structural obstacles in the form of limited access to initial capital and the complexity of licensing administration, these young coastal entrepreneurs have consistently practiced the five axioms of Islamic economics (Tawhid, 'Adl, Nubuwwah, Khilafah, and Ma'ad). Operational evaluation also shows that their trading system is highly consistent with the objectives of Maqashid Sharia, particularly the preservation of productivity Hifdzul Maal (safeguarding wealth) and the fulfillment of safety standards Hifdzun Nafs (safeguarding life), and is strictly free from the intrusion of the invalid (fasid) practices of MAGHRIB (Maysir [gambling], Gharar [uncertainty], and Riba [usury]).